Psychodermatology − biopsychosocial approach - Konstantine V. Aymedov (Journal of Education, Health and Sport, 2016)
Aymedov Konstantine V. Psychodermatology − biopsychosocial approach. Journal of Education, Health and Sport. 2016;6(12):941-950. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.321392